Positivity rate for COVID-19 of RT-PCR tests of the first quarter of 2021 of the state of Amazonas - Oliveira, Raquel Paiva de (Seven Editora, 2023)
The Ministry of Health (MoH) received the first notification of a confirmed case of Covid-19 in Brazil on February 26, 2020. Based on daily data reported by the State Health Secretariats to the Ministry of Health, from February 26, 2020, to May 15, 2021, 15,586,534 cases and 434,715 deaths from covid-19 were confirmed in Brazil. The pandemic in Brazil had already completed more than a year since the first reported case, but unfortunately, it was not possible to say that the situation was stable and that the epidemic was controlled in 2021 to opt for the relaxation of social isolation. In this sense, it is understood that testing in the population was a tool of great relevance to analyze whether cases were decreasing. The purpose of this research was to write the positivity rate for Covid-19 of the RT-PCR tests of the first quarter of 2021 in the State of Amazonas. The methodology used was a descriptive study using the e-SUS Notifica database. The results indicate that the average positivity of the State of Amazonas considering the tests carried out in the first quarter of 2021 was 36.47%, and the WHO recommendation is up to 5%, a level not reached by any Brazilian state. DOI:https://doi.org/10.56238/emerrelcovid19-009